Success Rate and Complications of Percutaneous Nephrolithotomy (PCNL) in Nephrolithiasis Patients - Stein, Lambok Kevin; Safriadi, Ferry (Majalah Kedokteran Bandung, 2025)
Percutaneous Nephrolithotomy (PCNL) is the standard management method for kidney stones due to its high success rates. This process is associated with risks, including complications such as infection and bleeding. This study aimed to evaluate the complications and success rates of PCNL in nephrolithiasis patients and provide important insights for clinical decision-making. Data were collected from patients undergoing PCNL for nephrolithiasis at Dr. Hasan Sadikin General Hospital Bandung, Indonesia, in the form of demographic data, stone parameters, and postoperative complications. Data were then analyzed statistically to identify the associated factors. This study was conducted at the Urology Department of the hospital from January to December 2023, involving 80 nephrolithiasis cases. Predominantly, 67.5% of patients were males, with 63.7% in the age group of above 50 years. Multiple stones were the most common (55%), with stone sizes of ≥1.5 cm prevalent in 95% of cases. Left-sided stones (43.75%) were most frequent, followed by right-sided (36.25%) and bilateral stones (20%). Hydronephrosis complications were present in 36.25% of cases, with 100% stone clearance found in Guy Stone Score (GSS) grade 1 cases, while GSS grade 4 cases exhibited the lowest stone clearance rate at 45.45%. This study provided insights into nephrolithiasis demographics, stone characteristics, and postoperative outcomes. Male predominance, multiple stones, high rates of stone clearance, and postoperative complications, particularly in the Guy's score system, underscore the need for proper management strategies and further research in this field.